Design for serviceability evaluation of car door - Chan, Seng Chang (2007)
Serviceability is the capability to perform effective problem determination,diagnosis, and repair on a system or a product. The main problem of Kancil's car door is the service cost and time are less consideration due to its uneasy disassemble and complexity procedures to service a car door. Design for serviceability evaluation of car door is aim to search for shorter car door service cycles and lower cost has led to the emergence of DFA and DFS. Through this project, DFS is a tool that will allow estimating the times and the cost for the service tasks which carrying out on the products. DFA will be analysis the optimization design to ease for assembly. DFA and DFS is the practice whereby the design needs to simultaneously consider various dotnstrearn activities throughout the entire product service life cycle, in addition to meeting the products' functions. Furthermore, Pugh method is concerned with finding the optimal and evaluate redesign concepts and thus to meet the serviceability requirements. A car door redesign has been presented to demonstrate the feasibility of the proposed scheme based on the easiest defect components on car door. The result shows that the service time of the current design, for instance door latch is 609.90s and after modification the service time reduces to 353.70s. While the service cost calculated with hourly labour rate before the modification is Rm20.85 and after modification is Rm20.49. Thus it can conclude that the proposed method can be applied on evaluating the product design at the early phase of the design.